The Effect of Learning Video Media On Social Emotional Development of Children Aged 5-6 Years - Nurhayati, Enung; Purwani, Annisa; Syahidin, Samin (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
Early childhood is a very decisive period in the formation of a child’s character and personality. At this time, the development of the potential of children is considered very important to lay the basic foundation of abilities for life in the future, one of which is the aspect of social-emotional abilities. Socio-emotional abilities will affect their behaviour in life and daily life. However, some children have not been able to interact well to express what is happening to themselves or their environment, have not been able to communicate and control and recognize their emotions, or help and cooperate with friends, if communicating is only done with only their close friends. For that, we need stimulation to increase it. Based on this, the researchers conducted a study that aims to determine how far the influence of learning video media is on the social-emotional development of students at RA Al-Hidayah. This study uses a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The variables studied were the Children’s Emotional Social abilities. The data collection technique used an observation sheet, which was used as a sample of 13 people from 26 people. The theoretical analysis used was theory from Daniel Goleman and also adapted to the Child Developmental Achievement Standards. The data obtained were processed using a twoparty t-test (Paired-Sample T-Test). The results of the research from the data found indicate that the percentage of students’ emotional, social abilities increases. The increase in students’ ability who use learning video media is 34.84 or up 71,44%, while students who do not use learning video media increase by 9.85 or 20,73%. The difference in the increase of the two groups was 24.99 or 50,71%. Furthermore, the results of data analysis using the t-test showed that the t count = (8,725) was more significant than the t table of (2,179). So it can be concluded that learning video media influences increasing social-emotional development in children aged 5-6 years at RA Al-Hidayah Pondoksalam Purwakarta. So the hypothesis states that the value of increasing the social-emotional ability of students who use learning video media is more excellent than students who do not use learning video media so that students’ emotional, social skills increase can be accepted.